Shape and fluctuations of frustrated self-assembled nano ribbons - Mingming Zhang (Nature Portfolio, 2019)
Supramolecular assemblies achieve nontrivial structures but there is no general framework to link their formation to molecular properties. Here the authors propose a model that relates molecular geometry and interactions to nanoribbon formation, validated by cryo-electron microscopy.